Influence of culture media, temperature and pH on Colletrotrichum gleosporioides, isolated from Carica papaya in Besut, Terengganu, Malaysia - Mohammad Hailmi, Sajili; Salmah, Mohamed; Noor Afiza, Badaluddin; Mohammad Moneruzzaman, Khandaker (2017)
Colletotrichum gleosporioides is known as the causal agent of anthracnose disease. Economic losses are reported during postharvest where the disease incidence and severity was recorded as 90-98 % and 25-38 % respectively. Colletotrichum spp. were isolated from lesions of infected Carica papaya L. that showing the typical anthracnose disease symptoms in Besut, Terengganu, Malaysia. Three types of fungal cultures were obtained that are identified as Colletotrichum sp., Fusarium sp. and Rhizoctonia sp. One of the fungal obtained was confirmed as Colletotrichum gleosporioides based on conidial morphology and growth characteristics on PDA media. The pathogen under study varied in its ability to grow under different environmental conditions. However, isolate preferred temperature range of 20°C to 30°C for the growth on PDA media. C. gloeosporioides isolates grew well at pH values within range of pH6 to pH 7.